What Is the Current State of Awareness, Knowledge, and Attitudes Toward Breast Cancer? A Cross-Sectional Survey Among Health and Non-health College Students - Islam, Md. Ashraful; AlShayban, Dhfer Mahdi; Nisa, Zeb-un-; Al-Hawaj, Ghadeer Abdulwahab Mohammed; Al-Eid, Ghadeer Hani Ali; Alenazi, Atheer Mohammed Moqbel; Malik, Zubda; Maqsood, Muhammad Bilal; Ishaqui, Azfar Athar; Akbar, Zahida; Iqbal, Muhammad Shahid; Hossain, Mohammad Akbar; et al. (Frontiers in Public Health, 2022)
Objective: To document breast cancer knowledge, awareness and attitudes from female undergraduate students studying in health and non-health subject colleges. Methods: A 3-months cross-sectional study was conducted among female undergraduate students studying at health and non-health subject colleges affiliated to a public university. Convenience sampling was employed, and a previously validated questionnaire available in English and Arabic languages, was used. Multiple linear regression was used to report predictors of breast cancer knowledge. A two-tailed p value of < 0.05 was considered significant. The study was approved by an ethics committee. Results: A total of 506 responses were analyzed. The mean knowledge score was 13.98 ± 4.1. The findings from the students surveyed highlight that more than 55% of the students had an acceptable level of knowledge. By breakdown based on education domain, roughly 70% and 40% of students from health and non-health colleges respectively, had an acceptable level of knowledge. The mean difference in knowledge score between students of health and non-health colleges was significant (p<0.001) as students from health colleges had higher score. The age, college type and, presence of the disease in family/relatives, were significant predictors of students’ breast cancer knowledge (p<0.05). Conclusion: Comparing it with previous evidence, it can be safely said that the knowledge of BC has significantly improved. The role of having awareness campaigns is greatly appreciated as it serves as a medium of information for students from non-health backgrounds. Moreover, internet and electronic media has emerged as a new source of information for non-health students and therefore, more efforts are needed to utilize this medium in empowering this student population in understanding of the disease.